Wanted dead and alive: Are hunting and protection of endangered species compatible? - Robinson, E (CSAE (University of Oxford), 2004)
This paper asks under what conditions it is possible for a wildlife department in west Africa without an external budget to protect all rare and endangered species, and if so, what is the impact on rural inhabitants engaged in hunting. Protecting wildlife in this region is particularly tricky. Hunting is important for rural livelihoods, but when unregulated can result in the loss of species. Government funding for wildlife departments is rarely sufficient and so they must increasingly look towards revenue-generating activities such as the sale of permits for hunting common species combined with fines for those caught with rare species.